A principled approach to state failure : international community actions in emergency situations - Giorgetti, Chiara (Developments in international law ;, 2010)
This book is the first legal study of state failure in international law. Dr. Giorgetti specifically analyses health, environmental and human rights emergencies and suggests concrete instruments for international actors facing emergencies in failing states. Her Principles for Action are an important contribution to the development of international law.